(untitled) (Ameghiniana, 2013)
A mandible of late Lujanian Age assignable to Tapirus terrestris is studied. The oldest record of Tapirus in South Ame rica correspond to the Ensenadan Age (early middle Pleistocene) of the Buenos Aires Province. The southernmost distribution of the genus (38° S. L.) is recorded in this period. The fossil here studied. has been found at 32° S. L.. that is , 4° more than the present southernmost distribution. The vertebrate assemblage s of the late Lujanian of Entre Ríos show import ant differences in taxonomy and frequency -du e to zoogeographical differences- respect to that of same Age in the Buenos Aires Province.